TINJAUAN YURIDIS TERHADAP KEABSAHANYA FORMAT STANDART KONTRAK PT. PERUSDA PDAM DENGAN KONSUMEN (STUDI PADA KANTOR PT. PERUSDA PDAM DI KOTA SAMARINDA) - Resty Dianisa (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTRegarding the validity of standard agreement which in this case the agreement between PDAM with the customer is actually if paid attention to contain weakness especially when connected or reviewed from Article 1320 BW Jo Article 1338 BW. It is said to contain weaknesses because in the standard agreement there is no consensus in the broad sense of the two sides, but only one-sided. While the applicant in giving the deal is just fictional. Thus standard agreement not only contains weakness, but also deviates from the principles contained in Article 1320 BW Jo article 1338 BW. So it can be said that the issue of validity of standard agreement when viewed from Article 1320 BW Jo Article 1338 BW formally can be said that standard agreement is not valid. However, we are faced with problems that inevitably recognize the existence of standard agreements as a means to meet the needs of many communities in supporting survival, economic growth is a vital means as the fulfillment of primary needs. The issue of the parties' attachment to a standard agreement is that the parties may agree to anything, provided that it is not contrary to law and morals, and that what is legally agreed is binding on the law. In connection with standard agreements held by PDAM and customers or consumers, as long as the standard agreement is agreed and no party is harmed, the agreement is considered valid as stated in article 1338 paragraph (1) of BW. Moreover, in the standard agreement that became the object of the agreement is a vital means (water consumed) which is a primary requirement that can not be ignored by all human in his life. It must be recognized its existence.